The impact of subsidaries, pricing and market structure on affordability and redistribution : the case of Cape Town road public transport - Eichhorn, Martin Thorne (School of Economics, 2016)
In an industry plagued by underinvestment and unrest, the emergence of the publicly financed MyCiTi Bus Rapid Transit system has structurally altered the market structure of Cape Town road public transport. Due to the heavy dependence of its rollout on subsidised operating support, and the geographies it has targeted, the distribution of subsidy benefits between households in the city has changed. In this context, this investigation looks to address the question: "Is Cape Town's road public transport affordable, and is subsidised operating support well targeted at poor households?" To do so, the paper evaluates the impact of the industry transition on transport affordability and subsidy distribution with the use of a best practice systematic framework. Revealed in the affordability analysis is that Cape Town road public transport remains unaffordable for the lower quartile of the household income distribution - a finding exacerbated by Cape Town's racial economic geographies. On top of this, distribution analysis shows the significant and regressive impact of the industry transition on the distributional consequences of Cape Town road public transport subsidisation. The central premise of this paper is that this evidence warrants the need to investigate alternative subsidy frameworks. Framed by Cape Town's underlying mobility needs and road public transport market structure, this paper designs and simulates the distributional consequences of an alternative subsidy. The simulation reveals that the regressive impact of the transition can be controlled, and the overall distribution improved, by deriving the subsidy framework by a set of demand-side variables. Rather than being viewed as the complete solution, the paper concludes that this simulation signals the need for follow-up research to validate the findings, and to explore the political and operational feasibility of a demand-side subsidy orientation more thoroughly.